Peranan Badan Kredit Desa (BKD) Terhadap Kesejahteraan Masyarakat Di Kecamatan Jombang - Supriyanto; Heru Widodo (Journal of Public Power, 2022)
The welfare of the people is an absolute national goal that must be achieved by the Indonesian nation. The services provided by the Village Credit Agency (BKD) are one of the breakthroughs in efforts to achieve community welfare in accordance with our national goals. The purpose of this study is: to find out the background of the emergence of the Village Credit Agency (BKD) and the extent to which the role of the Village Credit Agency (BKD) services for micro-enterprises in Jombang district. This research method is descriptive with a case study approach which is carried out to answer the problems that have been formulated. In this study, the authors use the people of Jombang District who are customers of the Village Credit Agency (BKD) in 20 (twenty one) villages in Jombang District by being represented or using the Village Credit Agency (BKD) customers of 4 villages, as many as 100 customers. The time used by the author is from August to September 2021. Data analysis technique uses regression analysis method. From the data analysis, it is known that the loan services provided by the village credit agency (BKD) have a significant role in the welfare of the community, especially micro-enterprises in Jombang District. The history of BKD is inseparable from the Dutch Government Regulation to minimize illegal credit that occurs in the community, BKD is an extension of BRI. In the regression analysis, it can also be proven that the credit provided has a significant role in the welfare of the community, especially micro-enterprises. From the analysis of the t test also shows the X2 variable obtained t count is greater than the t table, then Ho is rejected and Ha accepts. This means that the service of the village credit agency plays a significant role in the welfare of the community in Jombang District.